A review of keratoconus: Diagnosis, pathophysiology, and genetics - Mas Tur, Veronica; MacGregor, Cheryl; Jayaswal, Rakesh; O'Brart, David; Maycock, Nicholas (Survey of ophthalmology, 2017)
We discuss new approaches to the early detection of keratoconus and recent investigations regarding the nature of its pathophysiology. We review the current evidence for its complex genetics and evaluate the presently identified genes/loci and potential candidate gene/loci. In addition, we highlight current research methodologies that may be used to further elucidate the pathogenesis of keratoconus.